Rodchenko design - Milner, John 1946- (Design, 2009)
Alexander Mikhailovich Rodchenko (1891-1953) was a Russian artist, sculptor, photographer & graphic designer. Rodchenko was one of the most versatile Constructivist & Productivist artists to emerge after the Russian Revolution. This book focuses on Rodchenko's graphic work in the form of book jackets, posters & advertising.